2019
DOI: 10.1016/j.ultras.2018.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Four-dimensional optoacoustic monitoring of tissue heating with medium intensity focused ultrasound

Abstract: Medium-intensity focused ultrasound (MIFU) concerns therapeutic ultrasound interventions aimed at stimulating physiological mechanisms to reinforce healing responses without reaching temperatures that can cause permanent tissue damage. The therapeutic outcome is strongly affected by the temperature distribution in the treated region and its accurate monitoring represents an unmet clinical need. In this work, we investigate on the capacities of four-dimensional optoacoustic tomography to monitor tissue heating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Kim et al [147] designed a HIFU-living photoacoustic thermometry system with clinical US imaging with the feasibility of achieving safe and effective monitoring during the real-time treatment. Landa et al [148] demonstrated the optoacoustic monitored temperature variations with simultaneous thermocouple readings, and are regarded as 4D optoacoustic monitoring of tissue heating. Giurazza et al [149] conducted a preliminary analysis of thermometry based on ultrasound elastography and evaluated the feasibility of ultrasonic thermometry using specific ultrasound imaging technology based on elastography ARFI for laser ablation of biological tissue, though the results were not satisfactory.…”
Section: Real-time Temperature Monitoringmentioning
confidence: 99%
“…Kim et al [147] designed a HIFU-living photoacoustic thermometry system with clinical US imaging with the feasibility of achieving safe and effective monitoring during the real-time treatment. Landa et al [148] demonstrated the optoacoustic monitored temperature variations with simultaneous thermocouple readings, and are regarded as 4D optoacoustic monitoring of tissue heating. Giurazza et al [149] conducted a preliminary analysis of thermometry based on ultrasound elastography and evaluated the feasibility of ultrasonic thermometry using specific ultrasound imaging technology based on elastography ARFI for laser ablation of biological tissue, though the results were not satisfactory.…”
Section: Real-time Temperature Monitoringmentioning
confidence: 99%
“…shown to be sensitive to temperature variations. 140,141 This has been exploited to monitor hyperthermia-induced vasodilation in the human skin. 142 Multi-spectral OA imaging has been used…”
Section: Other Applicationsmentioning
confidence: 99%
“…Intravascular access is also possible, and dedicated probes can find important applications such as the characterization of human coronary atherosclerosis [12,150,166,167]. Potentially important diagnostic feature of the OA method is its high sensitivity to temperature variations as well as ability to spectrally differentiate coagulated tissues, which can be employed for monitoring ablation procedures and other thermal interventions [168][169][170][171][172][173].…”
Section: Perspectivementioning
confidence: 99%